Városfogalmak különböző tudományok látószögében, modernkori városhierarchiák - Bán, Gergely Károly (Hallgatói Műhelytanulmányok, 2022)
Bán, Gergely Károly: City concepts in the perspective of various disciplines, modern age urban hierarchies In today’s era of interdisciplinarity – when the break-up of formal boundaries between disciplines is a common phenomenon – it is not easy to find a common language, set of concepts and methods for different disciplines to use in their common research fields. A great example to this is the research of urban history, especially the research into city hierarchy. The complexity of this research topic is well illustrated by the fact that it is inherent in geography, history, sociology, statistics and economics. The different disciplines work with different definitions of the city, which are most definitely represented in research papers on urban history in the recent years. Legal (administrative), statistical, economic, sociological or geographic city concepts all have different understanding of the city. If we were to ask what discipline provides us with the most relevant, most fitting definition for the city as a settlement form then the answer would be: each of them. Why should not we talk about the definition of the city in the context of these city concepts, that is, administrative, statistical, sociological, etc. urban hierarchies? The aim of my study is to provide a complex picture of the potential urban hierarchy of the modern age.